PENGARUH RETURN ON ASSET DAN NET PROFIT MARGIN TERHADAP STRUKTUR MODAL PT. BPR TULUS - Ni Made Purnami; Laisa Liza (Politeknik Kutaraja, 2023)
This study analyzes the influence of ROA and NPM on the capital structure of PT. BPR TULUS. The data used consists of qualitative and quantitative data from primary and secondary sources. The data analysis technique employed is hypothesis testing. The results indicate that ROA has a non-significant negative effect on the capital structure. This suggests that the generated profits are primarily used to finance operational expenses rather than increasing capital or reducing debt. On the other hand, NPM has a significant positive effect on the capital structure. A higher NPM leads to a lower long-term debt to equity ratio. Based on these findings, it is recommended that the company carefully considers expenses and loan terms, taking into account the interest rate, in order to achieve more efficient profits when utilizing debt s operational capital.